Motherhood and the Allocation of Talent - Maria Inés Berniell; Lucila Berniell; Dolores De la Mata; María Edo; Yarine Fawaz; Matilde P. Machado; Mariana Marchionni (Institute of Labor Economics (IZA), 2021)
In this paper we show that motherhood triggers changes in the allocation of talent in the labor market besides the well-known effects on gender gaps in employment and earnings. We use an event study approach with retrospective data for 29 countries drawn from SHARE to assess the labor market responses to motherhood across groups with different educational attainment, math ability by the age of 10, and personality traits. We find that while even the most talented women— both in absolute terms and relative to their husbands—leave the labor market or uptake part-time jobs after the birth of the first child, all men, including the least talented, stay employed. We also find that motherhood induces a negative selection of talents into self-employment. Overall, our results suggest relevant changes in the allocation of talent caused by gender differences in nonmarket responsibilities that can have sizable impacts on aggregate market productivity. We also show that the size of labor market responses to motherhood are larger in societies with more conservative social-norms or with weaker policies regarding work-life balance.
Keywords: J13; J16; J22; J24; 330; child penalty; part-time; self-employment; motherhood; allocation of Talent